David Sox, "Quakers and the Arts: 'Plain and Fancy': An Anglo-American Perspective" - Book Review - Homan, Roger (Quaker studies, 2002)
David Sox, Quakers and the Arts: 'Plain and Fancy': An Anglo-American Perspective (York: Sessions, 2000), pp. viii + 127. Paperback £12.00. ISBN 1-85072-245-5.